Mindfulness, recovery-stress balance, and well-being among university dance students. Issue 1 (2nd January 2022) - Blevins, Peta; Moyle, Gene; Erskine, Shona; Hopper, Luke
ABSTRACT: Dance students face many physical and psychological stressors in their training and daily lives, therefore methods for coping with stress are essential for performance enhancement and general wellbeing. This study aimed to investigate the relationships between mindfulness, stress, recovery, and wellbeing among university level vocational dance students. Seventy-two dance students at two Australian universities completed online self-report measures of mindfulness, recovery-stress states, and affect. Correlation coefficients indicated a significant positive relationship between mindfulness and positive affect, and significant negative relationships between mindfulness and stress, and mindfulness and negative affect. MANOVA revealed differences between high mindfulness and low mindfulness groups on general stress, negative affect, and dance-specific recovery. The findings suggested that low mindfulness may be a risk factor for stress in general, and improvements in mindfulness may provide a protective buffer for students coping with a vast array of general and dance-specific demands.